2014
DOI: 10.1097/igc.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

PP242 Synergizes With Suberoylanilide Hydroxamic Acid to Inhibit Growth of Ovarian Cancer Cells

Abstract: These results suggest that the combination of SAHA and PP242 may lead to a novel strategy in treating patients with ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The results of the current study demonstrate that the role of PP242 in bladder cancer cells is more important for mTORC2, however further research is required to confirm the exact mechanism. Furthermore, numerous previous studies demonstrated that PP242 inhibited cell proliferation and induced apoptosis by its targeting of TORC2 (26)(27)(28)(29)(30). In order to confirm that PP242 targets mTORC2, the present study also examined the phosphorylation of mTOR.…”
Section: Discussionmentioning
confidence: 70%
“…The results of the current study demonstrate that the role of PP242 in bladder cancer cells is more important for mTORC2, however further research is required to confirm the exact mechanism. Furthermore, numerous previous studies demonstrated that PP242 inhibited cell proliferation and induced apoptosis by its targeting of TORC2 (26)(27)(28)(29)(30). In order to confirm that PP242 targets mTORC2, the present study also examined the phosphorylation of mTOR.…”
Section: Discussionmentioning
confidence: 70%
“…MORAB-003 (farletuzumab), which is a humanized anti-folate receptor alpha (FRα) monoclonal antibody derived from optimization of the LK26 molecule, contributed to human ovarian cancer cells (A2780, HeyA8, SKOV3ip1 and IGROV1) death associated with increased expression of LC3-II and enriched autophagic vacuolization in ovarian cancer [74]. Furthermore, cotreatment of suberoylanilide hydroxamic acid (SAHA) and PP242 inhibited growth of ovarian cancer cells (SKOV3 and A2780) synergistically by promoting LC3-II expression and decreasing p62 expression [77]. Likewise, combination treatment of a PARP inhibitor and a selective EGFR inhibitor erlotinib in ovarian cancer A2780 xenografts had an apparently enhanced antitumor effect via enhancing autophagy compared to their monotherapy [78].…”
Section: Autophagy and Ovarian Carcinomamentioning
confidence: 99%